Bobwhite Populations and Hunting on Illinois Public Hunting Areas - David Russel Vance; Jack A. Ellis (National Quail Symposium Proceedings, 2017)
Bobwhite (Colinus virginianus) populations on 2 public hunting areas in Illinois have been intensely utilized by hunters since 1964. Hunting has removed an average of 60-70%, and as much as 81%, of fall bobwhite populations, with no apparent detrimental effect on subsequent population levels. Total harvest and hunting effort were both closely correlated with prehunt quail abundance. Average hunter success was low (1 bird bagged per trip). The most successful hunters were resident of the regions surrounding the areas. The highest hunting success occurred on weekdays during the first week of the season.